The brothers Karamazov - Dostoyevsky, Fyodor, 1821-1881.; Garnett, Constance Black 1862-1946. (New York : Modern Library, 1996)
"The Brothers Karamazov, Dostoevsky's crowning achievement, is a tale of patricide & family rivalry that embodies the moral & spiritual dissolution of an entire society (Russia in the 1870s). It created a national furor comparable only to the excitement stirred by the publication, in 1866, of Crime & Punishment. To Dostoevsky, The Brothers Karamazov captured the quintessence of Russian character in all its exaltation, compassion, & profligacy. Significantly, the book was on Tolstoy's bedside table when he died. Readers in every language have since accepted Dostoevsky's own evaluation of this work & have gone further by proclaiming it one of the few great novels of all ages & countries. "'he Brothers Karamazov stands as the culmination of Dostoevsky's art: his last, longest, richest, & most capacious book,' said The Washington Post Book World. 'Nothing is outside Dostoevsky's province," observed Virginia Woolf. "Out of Shakespeare there is no more exciting reading.'" from inside flap.
Translation of: Brat'ia Karamazovy.
Date of publication from publisher's online site.
Keywords: Fathers and sons -- Fiction; Brothers -- Fiction; Patricide -- Fiction; Russia -- Social life and customs -- 1533-1917 -- Fiction; Didactic fiction